The impact of social isolation on the work of artists and teachers - Sass, Tamara (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The article is devoted to defining and understanding the changes caused by the pandemic that have occurred and are still taking place in the work of artists and teachers. The conclusions were formulated on the basis of direct interviews with representatives of the above-mentioned professional groups, and the selection of these groups was dictated by the increasingly stronger correlation of art and education in the era of the internet and multimedia, and the fact that both professional groups use art. For artists it is usually an end in itself, for teachers it is most often a tool to an end. The article summarizes the main concerns about the future and the possible benefits of working online.